Technology-assisted adaptive recruitment strategy for a large nation-wide COVID-19 vaccine immunogenicity study in Brunei - Shim, Chin Yee; Chan, Si Yee; Wei, Yuan; Ghani, Hazim; Ahmad, Liyana; Sharif, Hanisah; Alikhan, Mohammad Fathi; Haji Bagol, Saifuddien; Taib, Surita; Tan, Chee Wah; Ong, Xin Mei; Wang, Lin-Fa; et al. (Frontiers in Public Health, 2022)
A national study was conducted in Brunei to assess and compare the immunogenicity of the various brands of COVID-19 vaccines administered to the population as part of the National COVID-19 Vaccination Programme. Most of the population have had received at least 2 doses of BBIBP-CorV, AZD1222 or MRNA-1273 vaccines. Neutralising antibodies against SARS-CoV-2 induced by these vaccines will be analysed to infer population-level immune protection against COVID-19. During the 5-week recruitment period, 24,260 eligible individuals were invited to the study via SMS, out of which 2,712 participants were enrolled into the study. This paper describes the novel adaptive strategy used to recruit the study participants. Digital technology was leveraged to perform targeted online recruitment to circumvent the limitations of traditional recruitment methods. Technology also enabled stratified random selection of these eligible individuals who were stratified based on age, gender and vaccine brand. Data was extracted from the electronic health records, the national mobile health application and a third-party survey platform and integrated into a dedicated research platform called EVYDResearch. The instant availability and access to up-to-date data on EVYDResearch enabled the study team to meet weekly and adopt an adaptive recruitment strategy informed by behavioural science, where interventions could be quickly implemented to improve response rates. Some examples of these include incorporating nudge messaging into SMS invitations, involving the Minister of Health to make press announcements on this study, media coverage, setting up an enquiries hotline and reaching out to foreign language speaking expatriates of a local multinational company to participate in this study. Data integration from various data sources, real time information sharing and a strong teamwork led to good outcomes adaptable to the progress of recruitment, compared to the more time-consuming and static traditional recruitment methods.